The Cardiovascular Comorbidity in Children with Chronic kidney disease (4C) study: objectives, design, and methodology - Querfeld, Uwe; Anarat, Ali; Bayazit, Aysun K.; Bakkaloglu, Aysin S.; Bilginer, Yelda; Caliskan, Salim; Civilibal, Mahmut; Doyon, Anke; Duzova, Ali; Kracht, Daniela; Litwin, Mieczyslaw; Melk, Anette; et al. (Clinical journal of the American Society of Nephrology, 2010)
Background and objectives: Children and adolescents with chronic kidney disease (CKD) are at high risk for cardiovascular morbidity and mortality. A systemic arteriopathy and cardiomyopathy has been characterized in pediatric dialysis patients by the presence of morphologic and functional abnormalities. - Design, setting, participants, & measurements: The Cardiovascular Comorbidity in Children with CKD (4C) Study is a multicenter, prospective, observational study aiming to recruit more than 600 children, aged 6 to 17 years, with initial GFR of 10 to 45 ml/min per 1.73 m2. The prevalence, degree, and progression of cardiovascular comorbidity as well as its association with CKD progression will be explored through longitudinal follow-up. The morphology and function of the heart and large arteries will be monitored by sensitive noninvasive methods and compared with aged-matched healthy controls. Multiple clinical, anthropometric, biochemical, and pharmacologic risk factors will be monitored prospectively and related to the cardiovascular status. A whole-genome association study will be performed to identify common genetic variants associated with progression of cardiovascular alterations and/or renal failure. Monitoring will be continued as patients reach end-stage renal disease and undergo different renal replacement therapies. - Results: While cardiovascular morbidity in adults is related to older age and additional risk factor load (e.g., diabetes), the role of CKD-specific factors in the initiation and progression of cardiac and vascular disease are likely to be characterized with greater sensitivity in the pediatric age group. - Conclusions: The 4C study is expected to provide innovative insight into cardiovascular and renal disease progression in CKD.
Gesehen am 09.05.2023